Muscle strength mediates the relationship between mitochondrial energetics and walking performance. Issue 3 (9th February 2017) - Zane, Ariel C.; Reiter, David A.; Shardell, Michelle; Cameron, Donnie; Simonsick, Eleanor M.; Fishbein, Kenneth W.; Studenski, Stephanie A.; Spencer, Richard G.; Ferrucci, Luigi
Summary: Skeletal muscle mitochondrial oxidative capacity declines with age and negatively affects walking performance, but the mechanism for this association is not fully clear. We tested the hypothesis that impaired oxidative capacity affects muscle performance and, through this mechanism, has a negative effect on walking speed. Muscle mitochondrial oxidative capacity was measured by in vivo phosphorus magnetic resonance spectroscopy as the postexercise phosphocreatine resynthesis rate, kPC r, in 326 participants (154 men), aged 24–97 years (mean 71), in the Baltimore Longitudinal Study of Aging. Muscle strength and quality were determined by knee extension isokinetic strength, and the ratio of knee extension strength to thigh muscle cross‐sectional area derived from computed topography, respectively. Four walking tasks were evaluated: a usual pace over 6 m and for 150 s, and a rapid pace over 6 m and 400 m. In multivariate linear regression analyses, kPC r was associated with muscle strength (β = 0.140, P  =   0.007) and muscle quality (β = 0.127, P  =   0.022), independent of age, sex, height, and weight; muscle strength was also a significant independent correlate of walking speed ( P  <   0.02 for all tasks) and in a formal mediation analysis significantly attenuated the association between kPC r and three of four walking tasks (18–29% reduction in β for kPC r ). This is the first demonstration in human adults that mitochondrial function affects muscle strength and that inefficiency in muscle bioenergetics partially accounts for differences in mobility through this mechanism.